Comparison of the ellipsoid and simplex methods - Eligijus Laurinavičius; Danutė Raškinienė (Lietuvos Matematikos Rinkinys)
The ellipsoid method is presented. The least squers functional of the basic solution linear constrains is used as ellipsoid. The Klee-Minty linear programming problem is used to compare the ellipsoid and simplex methods.